2014
DOI: 10.1007/s00268-014-2708-7
|View full text |Cite
|
Sign up to set email alerts
|

Can New Inflammatory Markers Improve the Diagnosis of Acute Appendicitis?

Abstract: The conventional diagnostic variables for appendicitis, as combined in the AIR score, is an efficient screening instrument for classifying patients as low-, indeterminate-, or high-risk for appendicitis. The addition of the new inflammatory variables did not improve diagnostic performance further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 40 publications
2
45
0
1
Order By: Relevance
“…ROC curve for CA125 value for diagnosis of acute appendicitis routinely used at emergency departments. Other inflammatory mediators like interleukins and procalcitonin are evaluated for diagnosis of AA (3,4). However, in a meta-analysis they found no useful effect of several mediators on AA diagnosis (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROC curve for CA125 value for diagnosis of acute appendicitis routinely used at emergency departments. Other inflammatory mediators like interleukins and procalcitonin are evaluated for diagnosis of AA (3,4). However, in a meta-analysis they found no useful effect of several mediators on AA diagnosis (3).…”
Section: Discussionmentioning
confidence: 99%
“…Mainly leukocyte number and C-reactive protein are used for laboratory markers. However, they only show inflammation and are not specific to AA (3,4). There is still no specific laboratory or clinical marker of AA.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of leukocyte count and CRP assay helps to predict appendicitis inflammatory response score. 5,12,22 Various other biomarkers that are being studied include serum bilirubin level, D-dimer, pro-calcitonin, neutrophil to lymphocyte ratio, mean platelet volume, red blood cell distribution width, etc. It is important to understand here that most of these inflammatory markers are likely to be elevated/positive in many other inflammatory/infective conditions and are not specific to AA alone.…”
Section: Inflammatory Biomarkersmentioning
confidence: 99%
“…A multitude of widely divergent and at times conflicting publications discussing about the ideal diagnostic modality and treatment algorithm for AA are being added regularly in the scientific knowledge bank, which by itself is a testimony for the uncertainty that exists in this field today. [3][4][5][6][7][8] Without a clearly defined, universally accepted diagnostic algorithm for AA, a condition which is so common in our day to day practice, diagnosticians are at crossroads in selecting the right path. In this review, we intend to make an attempt to organize the approach to AA, especially with reference to the imaging diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Acute appendicitis is one of the most common causes of acute abdominal pain worldwide [1]. The reported lifetime cumulative incidence of acute appendicitis in Western countries is approximately 9%, and some recent reports have suggested that the incidence of acute appendicitis has been increasing in both developed and developing countries [2].…”
Section: Introductionmentioning
confidence: 99%